Effects of aircraft noise on the mental functions of schoolchildren - KOSZARNY, Zbigniew (Archives of Acoustics, 2016)
The levels of mental performance of children from two residential regions: in the neighbourhood of an airport, with a noise level of 95-105 dB (A) during the flight of a single aircraft, and a relatively quiet suburban Warsaw areas were appraised.A comparative analysis of the results of the investigations has revealeda considerable difference in the psychomotoric performances and attention level.For the inhabitants from the intensive noise area the lengthening of the time of a simple reaction, reduced visual and motoric coordination, disorder of psychomotoric control, and reduced ability of the concentrated and divided attention were observed.Experiments on the effects of intense noise have also revealed the detrimental influence of this noise upon all the aforementioned psychological processes for all people regardless of their acoustic environment. However, stronger effect of the experimental noise was found for children from the quiet areas and for children with an increased neuroticity.